Diskarte Skills Utilized by Parents and Caregivers Engaged in Home-Based Teaching During the COVID-19 Pandemic - Gomez, Marie Grace A (Alipato, A Journal of Basic Education; Vol 13 (2022), 2023)
This research identifies the levels of diskarte, a Filipino word denoting creative problem-solving with the aim of proposing a parent support program among 193 parents of students enrolled in different elementary public schools in Rizal, Philippines. These parents were engaged in home-based teaching during the COVID-19 pandemic. Using a descriptive-correlational design, the findings show that, generally, the parent participants in the study rated themselves to have a high level of diskarte. There is a significant difference in the levels of diskarte when grouped according to educational level. A Scheffe post hoc test revealed that there is a significant difference in the level of diskarte among parents who are elementary school graduates and those who have attained some college units, and parents who are elementary school graduates and college graduates. Diskarte skills seemed to enable the parents to have decreased stress in addressing the educational needs of their children engaged in modular learning. Among the diskarte skills mentioned was resourcefulness on where to get information when they could not understand the contents of the modules. They also demonstrated diskarte skills whenever they were faced with financial limitations on procuring devices and materials needed for their children’s remote learning.